Gut Microbiota Disorders Promote Inflammation and Aggravate Spinal Cord Injury Through the TLR4/MyD88 Signaling Pathway - Rong, Zijie; Huang, Yuliang; Cai, Honghua; Chen, Min; Wang, Hao; Liu, Guihua; Zhang, Zhiwen; Wu, Jiawen (Frontiers in Nutrition, 2021)
Background: In spinal cord injury (SCI), systemic inflammation and the death of nerve cells in the spinal cord are life threatening. The connection between gut microbiota and signaling pathways has been a hot research topic in recent years. The Toll-like receptor 4/Myeloid differentiation factor 88 (TLR4/MyD88) signaling pathway is closely related to the inflammatory response. This study explored whether the gut microbiota imbalance could affect the TLR4/MyD88 signaling pathway to regulate SCI to provide a new basis for SCI research and treatment. Methods: An SCI model was constructed to study the influence on the injury of gut microbiota. 16S amplicon sequencing was used to identify the diversity and abundance of gut microbes. Fecal microbiota transplantation was performed in mice with SCI. ELISA was used to detect the serum levels of pro-inflammatory and anti-inflammatory factors in mice. Hematoxylin and eosin staining was used to observe SCI in mice. Immunofluorescence was used to detect the rates of loss glial fibrillary acidic protein (GFAP), neuronal nuclear protein (NeuN), and ionized calcium-binding adapter molecule 1 (IBA1) in the spinal cord as indicators of apoptosis. The expression of the TLR4/MyD88 signaling pathway was detected by qRT-PCR and western blotting. Results: Significant differences were observed in the gut microbiota of SCI mice and normal mice. The gut microbiota of SCI mice was imbalanced. The levels of pro-inflammatory cytokines tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 in SCI mice were increased, as was the level of the toxic induced nitric oxide synthase. The levels of anti-inflammatory factors IL-4, transforming growth factor-β, and IL-10 were decreased, as was the level of arginase-1. The apoptosis rates of GFAP, NeuN, and IBA1 were increased. The TLR4/MyD88 signaling pathway was activated. In the SCI group, inflammation increased after fecal transplantation, apoptosis of GFAP, NeuN, and IBA1 increased, and SCI was more serious. Conclusion: The TLR4/MyD88 signaling pathway promotes the death of nerve cells by inducing inflammation. Gut microbiota dysregulation can lead to aggravated SCI by activating the TLR4/MyD88 signaling pathway.